The impact of working capital on the profitability of food and beverage companies in Malaysia / Norain Azwanah Abdul Jamarin - Abdul Jamarin, Norain Azwanah (2019)
This study is to study the impact of working capital on the profitability of the food and beverage companies in Malaysia. The property firm a selected form Bursa Malaysia listed firm, the number of companies selected is 29 companies. The study used secondary data for a period of five (5) years, from 2014 until 2018 and was analyzed by using the aid of STATA software. Based on the robust test results, there is four research hypotheses were formulated. Based on the research findings, the pooled regression model has been used to identify the result of a relationship between working capital management and firm’s profitability. The study found there is a significant relationship between Inventory Turnover, and Account Receivable Turnover with Return On Asset but insignificant relationship with Cash Turnover and Account Payable Turnover. The Cash Turnover and Account payable Turnover is not a major factor of the increasing in Return on Assets since the firm more prefer a buyer to purchase on credit which the firm is evaluate the profitable of a company by credit issue. Hence, the firm is recommended to monitor more to their business daily operation since the Food and Beverage is a short term financing.